2007
DOI: 10.1007/s00268-007-9224-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrence to the Lymph Node in Papillary Thyroid Carcinoma Patients without Preoperatively Detectable Lateral Node Metastasis: Validity of Prophylactic Modified Radical Neck Dissection

Abstract: Prophylactic MND is recommended for cases of papillary carcinoma demonstrating two or more of the following four characteristics; male gender, age 55 years or older, maximal tumor diameter larger than 3 cm, and massive extrathyroid extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
162
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(179 citation statements)
references
References 43 publications
(37 reference statements)
10
162
0
7
Order By: Relevance
“…In one study, it was reported that lymph node metastases were present in 40.5% of patients with microcarcinoma, even though the patients were diagnosed as node negative before surgery (141). [141][142][143]. In one study, multifocality, extrathyroidal extension, and lymph node metastasis at diagnosis were similarly prevalent in patients with PTMC and in those with larger papillary thyroid carcinomas (21).…”
Section: Clinical and Pathologic Characteristics Of Ptmc At Diagnosismentioning
confidence: 93%
See 1 more Smart Citation
“…In one study, it was reported that lymph node metastases were present in 40.5% of patients with microcarcinoma, even though the patients were diagnosed as node negative before surgery (141). [141][142][143]. In one study, multifocality, extrathyroidal extension, and lymph node metastasis at diagnosis were similarly prevalent in patients with PTMC and in those with larger papillary thyroid carcinomas (21).…”
Section: Clinical and Pathologic Characteristics Of Ptmc At Diagnosismentioning
confidence: 93%
“…The prevalence of extracapsular invasion and lymph node metastasis at diagnosis ranged between 2 (4) and 62.1% (112) and 0 (113) and 64% (8) respectively. In one study, it was reported that lymph node metastases were present in 40.5% of patients with microcarcinoma, even though the patients were diagnosed as node negative before surgery (141). [141][142][143].…”
Section: Clinical and Pathologic Characteristics Of Ptmc At Diagnosismentioning
confidence: 99%
“…Although PTMC is generally associated with an excellent prognosis, CLNM is common in PTMC patients with an incidence of 41-64% (12-17). There is no controversy in performing therapeutic neck dissection on cervical lymph node-positive PTMC patients to reduce the chance of persistence and recurrence (18), however debate remains as to whether CND should be performed on cN0 PTMC patients. A number of authors have proposed that there should be routine CND in patients with PTMC since there is evidence demonstrating that residual metastases in cervical lymph nodes represent the most common site of recurrent disease, and repeated operations may increase the incidence of operative complications, including hypoparathyroidism and damage to the laryngeal nerve (19).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies imply that the presence of lymph node metastases does not have any impact on the prognosis 31,32 . In contrast, other authors consider the presence of lymph node metastases a negative prognostic factor, especially in the case of bilateral and contralateral cervical lymph node metastases [33][34][35] . The prognosis in the case of affected nodes depends on the age, when the disease manifested.…”
Section: Tumor Sizementioning
confidence: 99%
“…Total thyroidectomy is required in the case of multifocal PTMC or tumors of higher TNM stage. This surgery allows postoperative optimization using the I-131 therapy, easier monitoring of the disease on the thyroglobulin levels, decrease in loco-regional recurrence, and improved prognosis 31,33,42 .…”
Section: Extent Of Surgerymentioning
confidence: 99%